Evaluation of Temperature Effect on Kernel Silo Dryer Towards Kernel Moisture Content at PT PQZ - Aini, Apsari Puspita; Sanjaya, Nady; Yahya, Agung Kurnia; Miftahurrahmah, MIftahurrahmah (Universitas Mulawarman, 2025)
This study aims to evaluate the effect of temperature on the Kernel Silo Dryer toward the moisture content of palm kernels at PT XYZ. Moisture control in palm kernels is crucial to ensuring optimal crude palm kernel oil (CPKO) quality. The drying process using a Kernel Silo Dryer was conducted at varying temperatures of 40°C, 50°C, and 60°C for three hours. Results indicated that higher drying temperatures resulted in lower kernel moisture content. At 60°C, the kernel moisture content reached the desired standard below 7%. However, at 40°C and 50°C, the moisture content exceeded the specified limit, increasing the risk of mould growth and reducing kernel quality. Key factors influencing drying efficiency include heater condition, steam pressure from the Back Pressure Vessel (BPV), and equipment cleanliness. Therefore, temperature optimisation and proper maintenance are essential to improve drying efficiency and maintain kernel quality.